HYBRID FIREFLY ALGORITHM-RNN TECHNIQUE BASED ACTIVE FILTER FOR PQ ENHANCEMENT - E, Veera Boopathy (Institute of Advanced Engineering and Science)
Shunt active power filter (SAPF) is utilized to compensate power quality (PQ) disturbances. For diminishing the PQ disturbances, the performance of SAPF must be enhanced. Here, a hybrid controller is employed to enhance the performance of SAPF and alleviates the PQ issues. The hybrid technique is the combination of firefly algorithm (FA) and recurrent neural network (RNN) technique. To minimize the PQ issue and to extract the reference current a hybrid method is employed. Furthermore, the dc link voltage is preserved at the constant level and harmonics are condensed. After that, the THD are evaluated for the proposed and conventional methods. The proposed method is executed in MATLAB/Simulink platform and their performances are computed. In order to prove the efficiency of the proposed method, this is compared with the conventional method such as, PI controller, Fuzzy controller and cuckoo search (CS)-radial basis function neural network (RBFNN) controller.